Maths 2000: topics book 3 - Domoney, Bill (Nelson Walton-on-Thames, 1996)
The full colour pupil material in this series is presented in a core number book and a core topic book for each year. The books are structured as a series of units of work, each with an introductory activity followed by a logical development of new ideas with open ended tasks.